Measuring the Perception of Bandung’s Community in Implementing the Smart Environment Concept - Osni Erza (International Journal of Small and Medium Enterprises and Business Sustainability, 2022)
This study aims to measure the perception of Bandung's community in implementing the smart environment (SE) concept. To measure the SE, the first step was to identify the city’s potential through observation, followed by a survey to analyze what indicators play a major role, and which SE dimensions need improvement. In this case, government policies are needed to invite the public to expedite the realization of a SE. This research used a mixed-method (quantitative and qualitative). The data were processed using SPSS and LISREL analysis tools using structural equation modeling (SEM). The testing was based on the theory of first-order confirmatory factor analysis and second-order confirmatory factor analysis. To support this quantitative data, the researchers conducted interviews with stakeholders to obtain data on the policies that have been carried out. The SE variable has 3 dimensions that have standardized factor loading which explains that all dimensions are meaningful and significant (valid), namely population density (0.51), environmental management - infrastructure (0.99), and the role of the community in environmental management (0.72). The reliability has been met with the value indicated by CR (0.80) and AVE (0.59).